Cannabis and athletic performance - Burr, J. F.; Cheung, C. P.; Kasper, A. M.; Gillham, S. H.; Close, G. L. (Sports Medicine, 2021)
Cannabis is widely used for both recreational and medicinal purposes on a global scale. There is accumulating interest in the use of cannabis and its constituents for athletic recovery, and in some instances, performance. Amidst speculation of potential beneficial applications, the effects of cannabis and its two most abundant constituents, delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), remain largely un-investigated. The purpose of this review is to critically evaluate the literature describing the effects of whole cannabis, THC, and CBD, on athletic performance and recovery. While investigations of whole cannabis and THC have generally shown either null or detrimental effects on exercise performance in strength and aerobictype activities, studies of sufficient rigor and validity to conclusively declare ergogenic or ergolytic potential in athletes are lacking. The ability of cannabis and THC to perturb cardiovascular homeostasis warrants further investigation regarding mechanisms by which performance may be affected across different exercise modalities and energetic demands. In contrast to cannabis and THC, CBD has largely been scrutinized for its potential to aid in recovery. The beneficial effects of CBD on sleep quality, pain, and mild traumatic brain injury may be of particular interest to certain athletes. However, research in each of these respective areas has yet to be thoroughly investigated in athletic populations. Elucidating the effects of whole cannabis, THC, and CBD is pertinent for both researchers and practitioners given the widespread use of these products, and their potential to interact with athletes` performance and recovery.